2008
DOI: 10.4161/psb.3.8.6337
|View full text |Cite
|
Sign up to set email alerts
|

Responses and tolerance to salt stress in bryophytes

Abstract: During exposure to salt environments, plants could perceive salt signal and transmit the signal to cellular machinery to activate adaptive responses. In bryophytes, salt signal components and transcript factor identified suggest that salt activate adaptive responses to tolerate adverse environments. The ability of bryophytes to tolerate salt is determined by multiple biochemical pathways. Transmembrane transport proteins that mediate ion fluxes play a curial role in ionic and osmotic homeostasis under salt env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…They attach to the polar terminal groups of membrane phospholipids and thus stabilize the membrane structure of moss cells under stressful conditions. In addition, high concentrations of sugars in the cell provide vitrification of the cytoplasm and membranes, which gives the cell structures stability and minimizes protein denaturation (Lobachevska et al, 2005;Wang et al, 2008;Bates et al, 2009). Carbohydrates also intercept reactive oxygen species and inhibit the processes of free radical oxidation of biological molecules during the development of oxidative stress induced by salinity.…”
Section: Discussionmentioning
confidence: 99%
“…They attach to the polar terminal groups of membrane phospholipids and thus stabilize the membrane structure of moss cells under stressful conditions. In addition, high concentrations of sugars in the cell provide vitrification of the cytoplasm and membranes, which gives the cell structures stability and minimizes protein denaturation (Lobachevska et al, 2005;Wang et al, 2008;Bates et al, 2009). Carbohydrates also intercept reactive oxygen species and inhibit the processes of free radical oxidation of biological molecules during the development of oxidative stress induced by salinity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that overexpression of the trehalose-6-phosphate phosphatase gene OsTPP1 confers salt, osmotic, and ABA tolerance in rice, and results in the activation of stress-responsive genes [42]. The conservation in the mechanisms of salt responses and stress tolerance has been observed between bryophytes and higher plants [43]. Some of the web sites for further study on salinity stress include:…”
Section: Salinity Stressmentioning
confidence: 99%
“…Under salinity conditions, high concentrations of Na + and Clions lead to hyperosmotic shock and ion imbalance. One of the main mechanisms regulating the concentration of sodium ions in cytosol is functioning of membrane pumps -H + -ATPases, which create the electrochemical gradient required to remove excess monovalent Na + ions outside the cells or into the vacuole [31]. It is also known that Na + is a major competitor of K + in the metabolic processes of cell.…”
Section: Introductionmentioning
confidence: 99%
“…In higher vascular plants, these genes were lost during the evolution process. It has been shown that under salinization conditions ion homeostasis in bryophytes cells was significantly dependent on the activity of H + -ATPase (PpSHP1 and PpSHP2) and Na + -ATPase (PpENA1 and PpENA2) [31]. It was experimentally proved that at Physcomitrella patens (Hedw.)…”
Section: Introductionmentioning
confidence: 99%